2021
DOI: 10.1101/2021.04.26.21256056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperreflective foci, OCT progression indicators in age-related macular degeneration, include transdifferentiated retinal pigment epithelium

Abstract: Age-related macular degeneration (AMD) is a common sight-threatening disease of older adults and treatment options are needed. Abnormalities of retinal pigment epithelium (RPE), supporting cells to photoreceptors and capillaries, are a hallmark. Clinical optical coherence tomography (OCT) imaging reveals hyperreflective foci (HRF) that confer risk for end-stage disease and are attributed to ectopic out-of-layer RPE. Using longitudinal OCT imaging of AMD patients, we demonstrate that the trajectory of one HRF f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 99 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…For example, a higher concentration of melanolipofuscin is found in foveal RPE (Bermond et al, 2020). Other studies using optical coherence tomography suggest that hyperreflective foci (potentially associated with AMD progression) may be due to migrating RPE cells undergoing transdifferentiation (Ouyang et al, 2013;Cao et al, 2021), highlighting the three-dimensional nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher concentration of melanolipofuscin is found in foveal RPE (Bermond et al, 2020). Other studies using optical coherence tomography suggest that hyperreflective foci (potentially associated with AMD progression) may be due to migrating RPE cells undergoing transdifferentiation (Ouyang et al, 2013;Cao et al, 2021), highlighting the three-dimensional nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether macular hyperpigmentation in AMD represents a single or diverse group of histopathologic abnormalities. Hyperpigmentation in CFP has been attributed to the proliferation of RPE cells and increased concentration of melanin‐containing organelles (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nine eyes with unremarkable central retinas were used for this study. Detailed methods based on our previous studies (Cao et al, 2021;Chen et al, 2022;Anderson et al, 2023) are shown in Supplementary materials.…”
Section: Chromogenic Immunohistochemistry Of Macula-wide Cryosectionsmentioning
confidence: 99%